Adsorptive removal of azithromycin from aqueous solutions using raw and saponin-modified nano diatomite - Davoodi, Siavash (Water science and technology : a journal of the International Association on Water Pollution Research, 2019)
This study aims to investigate the performance and mechanism of raw (R-ND) and saponin-modified nano diatomite (M-ND) in the removal of azithromycin from aqueous solutions. Adsorbent characterization was performed using X-ray fluorescence, Brunauer-Emmett-Teller (BET), scanning electron spectroscopy, dynamic light scattering and energy-dispersive X-ray analyses. It was shown that the specific surface area of R-ND was 119.5 m2/g, 14-fold higher than that for raw diatomite, and for M-ND it was 90.1 m2/g. Various adsorption conditions, i.e. adsorbent dosage, pH, initial concentration and contact time were investigated. According to the results, despite reducing the specific surface area by 25%, modification of nano diatomite by saponin markedly enhanced its performance in the removal of azithromycin. The maximum adsorption capacity of R-ND and M-ND in the removal of azithromycin was 68 and 91.7 mg/g, respectively. Fourier transform infrared spectroscopy results revealed that azithromycin was adsorbed by O-H groups on the diatomite surface. Weber-Morris intra-particle diffusion (IPD) model suggested that while IPD is not the rate-controlling step in high concentrations of azithromycin, it is the only step that controls the rate of adsorption in low concentrations. In comparison to R-ND, M-ND showed a higher efficiency in the removal of azithromycin and, therefore, it can be used as a promising low-cost adsorbent to remove azithromycin from aqueous solutions